(untitled) (Bangladesh Journal of Botany, 2023)
The initial geological analysis of hydropower projects is greatly complicated by the existence of complex geological conditions. To adapt advances in informatization and digitalization to the needs of the engineering survey industry and to conduct geological analysis more intuitively, in the present study the development of “GeoBIM”, a geological 3D design platform based on the DSI modeling engine and a “graphics + data” architecture is rerported. GeoBIM realized the integration of 3D information in the whole process of geological work, from field data collection, model design, and analysis to approval. Taking the siting and construction of a hydropower station as an example, the field data collection and cataloging APP (boreholes, caverns, slopes) and web-side exploration monitoring platform of GeoBIM were used to build a 3D geological fine visualization model. The principle of dissipated energy was used to analyze the quality of the rock mass, which showed the spatial distribution characteristics of local geological conditions and rock mass quality, improving the efficiency and intuitiveness of engineering rock mass quality classification. GeoBIM was compared with traditional 2D geological analysis methods and actual conditions to demonstrate the rationale and intuitive use of the 3D digital evaluation method in geological engineering. Bangladesh J. Bot. 52(2): 679-688, 2023 (June) Special